Evaluation of a Blood Reserve Protocol for Hip Fracture Surgery in the Elderly - Miyasaki, Maurício Rodrigues; Marques, Lucas de Quadros; Miranda, Thiago dos Santos; Ruiz, André Ruan; Fernandez, Karen Barros Parron; Biglia, Bruna (Revista Brasileira de Ortopedia, 2024)
Objective To identify the predictive factors for the need for transfusion during and after surgery to treat hip fractures in the elderly and to evaluate a protocol to guide the request for blood reserves for surgery.Methods The medical records of 172 elderly patients undergoing surgical treatment for proximal femoral fractures were collected. Data on sex, age, preoperative hemoglobin level, diagnosis, and type of surgery were tested for correlation with blood transfusion. In our sample, we determined the number of units of packed red blood cells reserved, the transfusion rate, and the cross-test:transfusion ratio. We made the same calculations in a hypothetical situation in which the request for blood reserves for our sample followed the criteria of a defined protocol.Results We found a correlation between the American Society of Anesthesiologists (ASA) classification and the occurrence of transfusions, and an inverse correlation between the hemoglobin level on admission and the number of bags transfused. A reserve of 328 units of packed red blood cells was requested for 167 surgeries. Had the proposed protocol been applied, 72 units would have been requested for 61 surgeries.Conclusion We found a correlation regarding the variables ASA classification and preoperative hemoglobin level and the occurrence of transfusion. Applying a proposed protocol to decide between requesting a reserve and only typing for elderly individuals undergoing surgical treatment for hip fracture proved suitable to reduce the number of packed red blood cell reserves.
Keywords: blood transfusion; blood typing; hip fractures